2017
DOI: 10.2166/wh.2017.011
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of human fecal marker GB-124 bacteriophages in urban sewage and reclaimed water of São Paulo city, Brazil

Abstract: Bacteriophages infecting Bacteroides fragilis GB-124 have been described as potential markers of human fecal contamination in water sources. The aim of this study was to evaluate the occurrence of GB-124 phages in raw sewage, secondary effluents and reclaimed water of the São Paulo city using a low-cost microbial source tracking method. Samples were collected monthly from April 2015 to March 2016 in four municipal wastewater treatment plants that operate with activated sludge processes followed by different te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Residual antibiotics in wastewater as pollutants can exert selective pressure and contribute to the increase in antibiotic-resistant bacteria [ 23 ]. Sewage from hospitals and the community, agricultural effluent and aquaculture wastewater are also important sources of resistant bacteria polluting the water sources [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Residual antibiotics in wastewater as pollutants can exert selective pressure and contribute to the increase in antibiotic-resistant bacteria [ 23 ]. Sewage from hospitals and the community, agricultural effluent and aquaculture wastewater are also important sources of resistant bacteria polluting the water sources [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The overall goal of this study was to establish low-cost, geographically suitable tools to identify potential pathways of exposure to human fecal contamination that could serve as transmission routes of typhoid fever in Kolkata. Whilst phages against Bacteroides strain GB-124 had previously been successfully detected in municipal sewage (untreated and treated) from England, Cuba, Ireland, France, Portugal, Denmark, Brazil, Spain, Italy, United States, and Uganda ( Ebdon et al, 2007 , 2012 ; Vijayavel et al, 2010 ; McMinn et al, 2014 ; Dias et al, 2015 , 2018 ; Purnell et al, 2016 ; Prado et al, 2018 ), the suitability of phages infecting GB-124 as indicators of human fecal contamination in India had not been characterized. The consistent detection of phages of GB-124 in sewage and a wide range of fecally contaminated environmental matrices, and its absence from pooled cattle, chicken, goat and dog feces suggest its potential as a culture-based indicator of human fecal contamination in Kolkata.…”
Section: Discussionmentioning
confidence: 99%
“…However, research has also shown that phages that are capable of lysing a specific host strain of Bacteroides in one part of the world, are not necessarily detected in samples of similar origin (or at similar levels) in other parts of the world ( Kator and Rhodes, 1992 ; Chung et al, 1998 ; Puig et al, 1999 ; Payan et al, 2005 ; Blanch et al, 2006 ), suggesting that different host strains may be needed for meaningful MST studies in different catchments or geographic regions. However, phages infecting certain B. fragilis strains (e.g., GB-124) have been shown to be restricted to human hosts ( Ogilvie et al, 2012 , 2018 ) and have been previously reported in Europe and North and South America as a potentially low-cost human fecal indicator ( Payan et al, 2005 ; Ebdon et al, 2007 , 2012 ; McMinn et al, 2014 , 2017 ; Prado et al, 2018 ). Geographic variations in the efficacy of MST markers have been reported in the extant literature ( Ebdon and Taylor, 2006 ; Harwood et al, 2013 ) due to potential differences in host genetics, antibiotic usage, immunological factors and dietary differences.…”
Section: Introductionmentioning
confidence: 99%
“…The exact origin of B. fragilis strain GB124 is unknown. It was isolated from untreated wastewater from a treatment plant in South East England and wastewater and impacted surface waters in the United Kingdom, United States, Brazil, and India (Payan et al, 2005;Prado et al, 2018;Wadhwa et al, 2018). Coupled with previously reported existence of a clear human gutassociated eco-genomic signature within the Bacteroides phage genomes (Ogilvie et al, 2012(Ogilvie et al, , 2013(Ogilvie et al, , 2018, it is assumed to be a human gut commensal.…”
Section: Discussionmentioning
confidence: 99%